Konflik Sosial dalam Komunitas Virtual di Kalangan Remaja - Dony Arung Triantoro (Jurnal Komunikasi, 2019)
The presence of virtual communities further facilitates interaction between individuals or groups. Interaction in the form of production, distribution, and consumption of messages in the virtual community has the chance of conflict. This study aims to analyze the causes of conflicts in virtual communities and how to overcome them. This study uses a qualitative approach. Data is collected through online participation, interviews, documentation and literature studies relevant to this study. This study found that social conflict in the virtual community of adolescents was caused by misunderstandings in understanding the text or opinions, sensitivity to symbols, time and community functions, cyberbullying, SARA issues and egocentric posts on differences in the background of community members. This conflict makes members of the virtual community fragmented into three groups, namely conservative, liberal and silent readers. There are various ways to deal with virtual conflicts that occur, including conciliation between perpetrators of conflict, mediation, temporarily removing actors from the virtual community to conduct detente by changing the subject or sending pictures that invite other members to laugh. Keywords: Social Conflict, Virtual Community, Adolescent